Selection of the most productive nutrient media for the cultivation of predatory nematodes - Zhappar, N.K.; Shaikhutdinov, V.M.; Asherbekova, L.K.; Khassenova, A.E.; Shibaeva, A.K. (Fundamental and Experimental Biology, 2022)
Modes of mass production of entomopathogenic nematodes isolated from various habitats of Akmola and Pavlodar regions were tested. As a result of the selection of nutrient media and cultivation conditions of entomopathogenic nematodes, the largest populations of nematodes (more than 100,000 young individuals/ml) were obtained on medium C11 containing yeast extract (23 g/l), egg yolk (13.5 g/l), and corn extract (40 g/l). On the 20th day of cultivation, the maximum concentration of viable nematodes was reached (123 856, 127 572, and 122 469 nematodes/ml for isolates AF 29, AF 57, and KP 76, respectively), which was main-tained until the end of the experiments. During the process, the initial concentration of nematodes increased by more than 2 orders of magnitude. When working out the modes of mass production of nematodes on a semi-industrial scale, the populations of isolates AF 29, AF 57, and KP 76 in media amounted to 122 754, 131 784, and 126 521 nematodes per ml. The total volume of the resulting preparation was 50 liters. The ob-tained results are applicable in crop production in the fight against potato pests.